Effectiveness of regional government authority regarding mining business permits post presidential decree number 55 of 2022 concerning mineral and coal mining management - Darman, Melani; Riyanti, Indah (Institute Of computer Science (IOCS), 2024)
The mining business is a business that has the most layers of regulations. This is because in addition to the various types of mining, it is also because the mining processing process is so complex. Judging from the legal review, the mining regime has experienced very significant changes. At that time, the mining regime used a contract of work model between mining companies and the government, both local and central government. In practice, contracts of work provide opportunities for mining companies to control mining areas for a certain period of time. At this time the mining regime is the licensing regime. This was marked by the issuance of Law No. 4 of 2009 concerning Minerba. Based on the law, the relationship between mining companies and the government is no longer a partner relationship, but rather a government administration relationship. In the process of perfecting the legal system, in 2022, the government will again issue a regulation regarding the delegation of authority from the central government to regional governments with regard to the management of mineral and coal mining. This Government Regulation is considered very appropriate and effective. Mining of non-metallic minerals and coal involves many small-scale mining companies or small-scale mining companies. So it is hoped that permit arrangements will be adjusted to the needs of small-scale mining